LEGISLATIVE EFFECTIVENESS AND THE ROLE OF PERU'S CONGRESS: THE CASE OF DECLARATIVE LAWS - Abensur Pinasco, Jaime Americo (2025)
The present research had as its general objective to determine how the declarative laws approved by the Congress of Peru achieved real legislative effectiveness in Peruvian society. To do so, a qualitative approach and an exploratory design were used, considering as a population the declarative laws approved by Congress since 2016. The sample would be 12 declarative laws approved between 2016 and 2023, finding that these declarative laws had a significant impact on Peruvian society. It was highlighted that the declarative laws of infrastructure generated a tangible change in the execution of works, benefiting various sectors of the citizenry in Peru. Concluding that declarative laws are legal norms that, fundamentally, stand out for their ability to alert the executive branch on specific issues. They not only seek to ensure the realization of concrete actions, but also promote economic and cultural development in areas that need attention.